2004
DOI: 10.4161/cc.4.1.1366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Smad Antiproliferative Function by CDK Phosphorylation

Abstract: Rb family members were the only demonstrated substrates of CDK4 until it was shown recently that Smad3, which plays a key role in mediating TGF-β antiproliferative responses, is phosphorylated by both CDK4 and CDK2 in vivo and in vitro. CDK phosphorylation of Smad3 inhibits its transcriptional activity and antiproliferative function. The Rb pathway is disrupted in almost all human cancers. Most cancers contain high levels of CDK activity due to frequent inactivation of the p16 tumor suppressor or overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 51 publications
(149 reference statements)
2
34
0
1
Order By: Relevance
“…Consistent with this hypothesis Liu et al (32,33) have shown that CDK4 and CDK2 phosphorylation of Smad3 inhibits its antiproliferative effects. Whether reduction of p15…”
Section: (K5cdk4/cdk2supporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with this hypothesis Liu et al (32,33) have shown that CDK4 and CDK2 phosphorylation of Smad3 inhibits its antiproliferative effects. Whether reduction of p15…”
Section: (K5cdk4/cdk2supporting
confidence: 63%
“…Ink4b transcription can be down-regulated via phosphorylation and inactivation of Smad3 by CDK4 (32,33), but decreased p15 Ink4b was observed in both K5CDK4 and K5CDK4/ CDK2 À/À , suggesting that its down-regulation is not responsible for the CDK4-induced malignant progression.…”
Section: Discussionmentioning
confidence: 98%
“…Disruption of this 'p16-cyclin D1-RB' axis is known to occur in the majority of human tumors (Palmero and Peters, 1996;Sherr and McCormick, 2002), thus underscoring the importance of this pathway in growth regulation. Several additional substrates of CDK4/cyclin D1 have been identified, including Smad3 (Liu and Matsuura, 2005), CDT1 , and the RB-related proteins p107 Leng et al, 2002) and p130 (Canhoto et al, 2000). Each putative substrate harbors an established role in cell cycle control and therefore may influence tumorigenesis.…”
Section: Cyclin D1 and Cell Cycle Controlmentioning
confidence: 99%
“…An unbiased screen for CDK4 and CDK6 substrates yielded 68 potential phosphorylation targets, in addition to pRB, p107, and p130 (34). Several of these putative substrates, including FOXM1 and SMAD3, have been implicated in senescence signaling (34)(35)(36). Thus, the tumor-suppressive activities of CDK4/6 in pRB/p107/p130-defective cells may be mediated through one or several of these, or involve as yet unidentified pathways (Fig.…”
Section: Cervical Cancer Cells Are Sensitive To Treatment With the Kdmentioning
confidence: 99%